Bullying and behavioural conflict at work : the duality of individual rights - Barmes, Lizzie (Oxford : Oxford University Press, 2016)
Based on extensive empirical research examining behavioural conflict at work, this book gives a much-needed insight into the current law that regulates workplace behaviour. Arguing that current law and policy is insufficient, the author suggests reforms which seek to reconcile individual and collective perspectives on working life.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 11, 2015).
Keywords: Bullying in the workplace -- Law and legislation -- Great Britain; Law; Laws of specific jurisdictions & specific areas of law